2020
DOI: 10.1007/s11367-020-01807-8
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life modelling of buildings to support more informed decisions towards achieving circular economy targets

Abstract: Purpose Life cycle assessment (LCA) is an internationally accepted method to assess the environmental impacts of buildings. A major methodological challenge remains the modelling of the end-of-life stage of buildings and allocation of benefits and burdens between systems. Various approaches are hence applied in practice to date. This paper compares the two methods widely renowned in Europe—the EC product environmental footprint (PEF) method and the CEN standards: EN 15804+A1 and EN15978—and offers insights abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 20 publications
(25 reference statements)
0
18
0
1
Order By: Relevance
“…Contrarily, this study has shown that limited databases can significantly impact the EC calculation outcome [45]. This lack of data can be attributed to the comparatively long building useful lifespan and uncertain nature of the EoL processes or activities [46]. Although the use of default national EoL values and assumptions enable EoL modelling and reduce the time required in performing LCA, the lack of data sources providing ECFs hampers the reliability of assessment results.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Contrarily, this study has shown that limited databases can significantly impact the EC calculation outcome [45]. This lack of data can be attributed to the comparatively long building useful lifespan and uncertain nature of the EoL processes or activities [46]. Although the use of default national EoL values and assumptions enable EoL modelling and reduce the time required in performing LCA, the lack of data sources providing ECFs hampers the reliability of assessment results.…”
Section: Resultsmentioning
confidence: 94%
“…In their study to model the end-of-life phase of buildings and allocate benefits and burdens, Mirzaie et al [46] found that information in generic databases concerning EoL activities such as deconstruction, transportation, recycling, and disposal, in many cases, is little or non-existent. Considering that concrete forms the larger proportion of this supermarket building, recycling concrete can further reduce the life cycle carbon emissions [30].…”
Section: Resultsmentioning
confidence: 99%
“…also used CFF as one of the EoL modeling approaches for buildings, to achieve circular economy targets. [ 83 ]…”
Section: Methodsmentioning
confidence: 99%
“…[82] Mirzaie et al also used CFF as one of the EoL modeling approaches for buildings, to achieve circular economy targets. [83] Accorsi et al [36] Huang et al [84] Impact factors of sustainable design and development of plastic molds Almeida et al [85] Material selection for beverage packaging Foschi et al [86] Integrated decision-making process in packaging redesign Alpizar et al [87] Policy instruments for decision-making to curb marine litter Sherwood et al [88] Recirculation and sustainable product design for bio-based products Vogt et al [89] Redesign polymers and key challenges for advancement of plastic recycling Leal et al [90] Indicator based product design approach to improve circular economy Antonopoulos et al [91] Factors affecting the recycling of post-consumer plastic packaging waste Löw et al [92] Guidelines and implementation of DfR in plastics Mendes da Luz et al [93] Methodology to integrate LCA in the product development process…”
Section: Literature Reviewmentioning
confidence: 99%
“…Module D [13]) and the Product Environmental Footprint (PEF) method [14] applies a generic system expansion approach for all industrial sectors including the construction sector, that does not allow for modeling multiple life cycles (e.g., PEF [14]). There are issues with deciding on end-of-life calculations, end-of-waste of various materials [15] and available life cycle assessment tools do not have a straightforward way for extending lifetime of buildings and building elements e.g., Belgian TOTEM, a life cycle assessment tool used to facilitate LCA in architectural practice [16]. A common representation of impacts in LCA is the bar graphs that represent total impacts per impact category per functional unit.…”
Section: Introductionmentioning
confidence: 99%